EFEK MEDIA SOSIAL PADA PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG TEKNIK MENGURANGI RASA NYERI PERSALINAN - Zahrah Zakiyah; Dheska Arthyka Palifiana; Sitti Khadijah (Universitas Respati Yogyakarta, 2021)
The Social Media Effect on Increased Maternal Knowledge of Techniques that Reduce Labor PainBackground: pain during childbirth is one of the most painful pains compared to other pain experienced by women during their lifetime. A woman will perceive pain depending on her cognitive and emotional. Cognitive and emotion are closely related to knowledge. Knowledge is one of the factors that influence pain. Small discussion groups or classes for pregnant women are used as a means of sharing knowledge. The use of social media is an alternative option that can be used to keep discussion groups or classes on pregnant women alive without being hindered by situations and conditions. Objective: To determine the effectiveness of social media to increase knowledge of pregnant women on techniques to reduce labor pain. Method: This is a Pre-Experimental Designs research with the type of One-group Pretest-posttest design. Research respondents were primigravida pregnant women who were collected in a Whatsapp Group (WAG) group as a medium of communication and learning during the Covid-19 pandemic. The pretest was carried out on the research respondents before the treatment in the form of providing information on techniques to reduce labor pain, and the posttest was carried out after the treatment was carried out. Data analysis used paired T-test. Results: there are differences in the level of knowledge of respondents before and after treatment. Before treatment, it was known that the average value of the respondents was 51.42±13.88 with the highest value of 70, while after treatment the average value was known to be 67.28±13.57 with the highest value of 90. The ρ-value was 0.002. Conclusion: social media has proven to be effective to be chosen as a means of transferring knowledge without being hindered by environmental situations and conditions.